Developing Strategies for Building a Tone of Voice for Brands in Southeast Asia - Padres Gonzalez, Miquel (Graduate School of Institut Seni Indonesia Yogyakarta, 2024)
This paper explores the strategies necessary for creating an effective tone of voice for brands with a regional presence in Southeast Asia. Considering the diverse cultural, ethnic, and religious landscape, the study emphasizes the importance of understanding linguistic nuances, audience segmentation, aspirational values, and political contexts to craft brand messages that resonate with local consumers. Through a mixed-methods approach that includes qualitative interviews, focus groups, and quantitative surveys, the research identifies key cultural and linguistic factors influencing brand communication in countries such as Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam. The findings reveal that preferences for tone vary significantly across countries, with a general preference for formal tones in Malaysia and Thailand, while humor resonates more in the Philippines and Vietnam. Additionally, religious and aspirational values strongly influence brand perception, particularly in Indonesia and Malaysia. Overall, the results suggest that a flexible and culturally sensitive approach is essential for successful brand communication in this region. The paper also discusses the challenges and opportunities of managing linguistic diversity and provides practical guidelines for developing a brand tone of voice that can be effectively applied across different markets. By incorporating insights on how to address various audience segments and religious considerations, the study aims to equip brand managers with the tools needed to build a cohesive and resonant brand identity in Southeast Asia. Mengembangkan Strategi untuk Membangun Nada Suara bagi Merek di Asia TenggaraAbstrak Makalah ini mengeksplorasi strategi yang diperlukan untuk menciptakan nada suara yang efektif bagi merek-merek dengan kehadiran regional di Asia Tenggara. Mengingat keragaman budaya, etnis, dan religi, studi ini menekankan pentingnya memahami nuansa linguistik, segmentasi audiens, nilai-nilai aspiratif, dan konteks politik untuk merumuskan pesan merek yang dapat beresonansi dengan konsumen lokal. Melalui pendekatan metode campuran yang mencakup wawancara kualitatif, kelompok fokus, dan survei kuantitatif, penelitian ini mengidentifikasi faktor budaya dan linguistik kunci yang memengaruhi komunikasi merek di negara-negara seperti Indonesia, Malaysia, Filipina, Singapura, Thailand, dan Vietnam. Temuan menunjukkan bahwa preferensi untuk nada bervariasi secara signifikan di berbagai negara, dengan preferensi umum untuk nada formal di Malaysia dan Thailand, sementara humor lebih beresonansi di Filipina dan Vietnam. Selain itu, nilai-nilai religius dan aspiratif sangat memengaruhi persepsi merek, terutama di Indonesia dan Malaysia. Secara keseluruhan, hasilnya menunjukkan bahwa pendekatan yang fleksibel dan sensitif terhadap budaya sangat penting untuk komunikasi merek yang sukses di kawasan ini. Makalah ini juga membahas tantangan dan peluang dalam mengelola keragaman linguistik dan memberikan pedoman praktis untuk mengembangkan nada suara merek yang dapat diterapkan secara efektif di berbagai pasar. Dengan memasukkan wawasan tentang cara mengatasi berbagai segmen audiens dan pertimbangan religius, studi ini bertujuan untuk membekali manajer merek dengan alat yang diperlukan untuk membangun identitas merek yang kohesif dan beresonansi di Asia Tenggara.